CHARACTERIZATION OF ZINC OXIDE NANOPARTICLES SYNTHESIZED BY OLEA EUROPAEA LEAVES EXTRACT (PART L) - Al-Ghareebawi, A. M.; Al-Okaily, B. N.; Ibrahim, O. M. S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
The current study was aimed to synthesized zinc oxide nanoparticles (ZnONPs) using aqueous extract of olive leaves (OLE), which is very simple and eco-friendly method. ZnONPs were formed by dissolving of OLE in zinc oxide solution with adjusted pH to 12. Zinc acetate dehydrate reduced to ZnONPs during mixing with OLE associated with change of the color solution from white to pale yellow color within a few minutes. The synthesized OLEZnONPs were separated by centrifugation (4000rpm/ 5min) , then characterized by Fourier Transmission Infrared Spectroscopy (FT-IR), X-ray diffraction (XRD) and Field emission-Scanning Electron Microscopy (FE-SEM) methods. The results of FT-IR showed that the functional group related to Zn-O at (433.98 to 416.67 cm_1), whereas X-RD at 2 theta diagnose the type of oxide formation as ZnO and determined particle size in range (20 – 30 nm). Besides, SEM image was showed the presence of hexagonal shape of ZnO nanoparticles (42.87nm). Therefore, the biogenic synthesis of zinc oxide nanoparticles using Olea Europaea leaves was simple, low coast, can be an alternative to chemical synthesis and the possibility of using in biomedicine field